2018
DOI: 10.21833/ijaas.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Turnover intentions in Jordanian Universities: The role of leadership behaviour, organizational commitment and organizational culture

Abstract: Evidence gathered in relation to academic situation in Jordan is alarming. About 3000 Jordanian academics left their job during the last 25 years. During the last eight years, twenty percent of working academics were planning to search for opportunities in other, mostly foreign, universities. This particular percentage is expected to increase to more than 60% by the end of 2020. Although low turnover rates are beneficial by opening doors for new talents and new ideas, high rates are disruptive and negatively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 62 publications
1
21
1
Order By: Relevance
“…Rather costs are either hidden or unmeasured. Hidden costs of voluntary turnover include new recruitment and selection of employees, temporal staffing and training of new recruits while unmeasured costs include loss of customers and human capital knowledge which does not come under calculation (Alzubi, 2018;Holtom et al, 2008). Estimation of such losses is varied for every organization.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Rather costs are either hidden or unmeasured. Hidden costs of voluntary turnover include new recruitment and selection of employees, temporal staffing and training of new recruits while unmeasured costs include loss of customers and human capital knowledge which does not come under calculation (Alzubi, 2018;Holtom et al, 2008). Estimation of such losses is varied for every organization.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Participative leadership style highly regards delegation of duties and responsibilities. It also involves people in decision making (Dubrin, 2017). Employees feel more satisfied in the work place if they are involved in making key decisions that affect them.…”
Section: Participative Leadershipmentioning
confidence: 99%
“…Article [22] The reasons for which academics quit jobs, in the context of the impact of leadership, organizational commitment and organizational culture are examined. It is concluded that the leaders should recognize the leadership impact, as leaders' behavior can motivate the commitment of higher school employees and reduce the turnover intentions Article [23] Organizational Culture…”
Section: Thematic Changes In the Spectrum Of Research On Organizationmentioning
confidence: 99%